Lessons Learned and Recommendations from a SCOPE Spinal Cord Injury Neurorestorative Clinical Trials Update - Bethany R. Kondiles; Sabhya Rana; David Weiner; Armin Blesch; James St. John; Cornelia Haag-Molkenteller; Patrick Freund; James Guest; Daniel D. Mikol; Susan Harkema; Randy D. Trumbower; Michael G. Fehlings; et al. (Neurotrauma Reports)
The Spinal Cord Outcomes Partnership Endeavors presented a clinical trials update (CTU) in collaboration with the International Spinal Research Trust as a precourse to their annual meeting. Selected trials adhered to a priori considerations, prioritizing novelty and a focus on neurorestorative approaches. The sessions featured 13 speakers, covering 4 in-preparation, 4 in-progress, and 4 recently completed trials. In addition to in-person attendance, individuals worldwide viewed a live stream of the presentations. Approximately 1600 participants, comprising clinicians, researchers, industry stakeholders, foundations, and individuals with lived experiences, engaged in the CTU through both in-person and virtual channels. Presentations represented a variety of approaches, including drug, biological, and device-based therapeutics. This summary provides high-level summaries of the trials presented and the resulting discussions including lessons learned. Rather than recapitulating published data, the presentations and discussions emphasized the novelty and strengths of each trial, practical aspects of translation, and lessons learned. Throughout the day, several discussion themes surfaced. These included reflections on the suitability of outcome measures and the distinction between statistically or clinically meaningful effects and meaningful changes in quality of life. Additional topics included novel trial designs, selection of inclusion criteria, recognizing the indispensable role of rehabilitation, tailoring approaches to individual needs, the importance of integrating lived experience, and emphasizing the importance of establishing robust pre-clinical data packages before venturing into clinical translation. Importantly, strategic directives are summarized to address these challenges, focusing resources and efforts to steer forthcoming trials effectively.